Ali Hasjmy dan Konsep Kekuasaan dalam Islam - Mukhtar, Mukhtar (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
This paper wishes to explain the political concept of Islamic power by Ali Hasjmy who can describe the basis of the ideal state contained in Islamic teachings in order to influence the state system without having to recognize the identity itself. The main focus is how mechanisms in Islamic state thinking can influence the concept of power and country. This paper uses a research method that prioritizes library research into primary data that is data collection method by finding information through books, magazines, newspapers and other literature that aims to form a theoretical basis (Arikunto, 2006). The results of this study found that the concept of power according to Ali Hasjmy emphasized the participation and cooperation of the people in the implementation of deliberation. Deliberation in formulating problems for the state, so that the role of shura in the Islamic view becomes an ideal alternative in the implementation of a country. Thus the mechanism of shura is almost the same as the democracy because it lays the voice of the ummah as the ultimate decision maker.